Review of Environmental Aspects and Community Behavior in the Determination of Filariasis Risk Vulnerability Zone (Unnes Journal of Public Health, 2018)
ABSTRACT Pekalongan City is a filariasis endemic area with the highest number of filariasis cases in Central Java. One of the factors influencing the risk of transmission of filariasis is environmental factors and community behavior. The purpose of this research was to know the potential areas of filariasis transmission risk in terms of environmental condition and behavior of society. This research was conducted on 6 urban villages in Pekalongan City on May-June 2017. It was quantitative descriptive research based on Geographic Information System (GIS) with the object of research in the form of environmental factors and community behavior in the mapping unit. The sample technique used proportional random sampling with 387 respondents in a sample area. Data analysis used univariat and spatial analysis with buffer, overlapping and overlay techniques. The result of this study were still there region that categorized very vulnerable to transmission of filariasis with amount each variable as many as 55.3% (21 RWs) based on sewerage condition, 57.8% (22 RWs) based on the presence of stagnant water, 23.7% (9 RWs) based on the night outdoor habit, 86.9% (33 RWs) based on the habit of using mosquito nets, and 39.5% (15 RWs) based on the overlay of vulnerability to environmental conditions and community behavior. ABSTRAK Kota Pekalongan merupakan daerah endemik filariasis dengan jumlah kejadian filariasis tertinggi di Jawa Tengah. Salah satu faktor yang mempengaruhi tingkat risiko penularan filariasis di Kota Pekalongan adalah faktor lingkungan dan perilaku masyarakat. Tujuan penelitian ini adalah untuk mengetahui daerah potensial penularan filariasis ditinjau dari kondisi lingkungan dan perilaku masyarakat. Penelitian ini dilakukan pada 6 kelurahan di Kota Pekalongan pada bulan Mei-Juni 2017. Jenis penelitian ini adalah penelitian deskriptif kuantitatif berbasis Sistem Informasi Geografis (SIG) dengan objek penelitian berupa faktor lingkungan dan perilaku masyarakat dalam unit pemetaan. Pengambilan sampel perilaku dilakukan dengan teknik proporsional random sampling menggunakan sampel wilayah terdahap 387 responden. Analisis data menggunakan analisis univariat dan analisis spasial dengan teknik buffer, pengharkatan dan overlay. Hasil penelitian menunjukkan bahwa masih terdapat wilayah yang masuk kategori sangat rentan penularan filariasis proporsi sebanyak 55,3% (21 RW) berdasarkan kondisi SPAL, 57,8% (22 RW) berdasarkan keberadaan genangan air, 23,7% (9 RW) berdasarkan kebiasaan keluar rumah pada malam hari, 86,9% (33 RW) berdasarkan kebiasaan memakai kelambu, dan 39,5% (15 RW) berdasarkan overlay kerentanan kondisi lingkungan dan perilaku masyarakat.